1) xy^{' }+y=e^{(2x) }-sinx solve this equations...

2)y(x^{2}y^{2}+2)dx+x(2-2x^{2}y^{2})dy=0 solve this equations

Thank you for all help..

B/r

Printable View

- Oct 11th 2012, 09:31 PMvaveylaDif.Equations
1) xy

^{' }+y=e^{(2x) }-sinx solve this equations...

2)y(x^{2}y^{2}+2)dx+x(2-2x^{2}y^{2})dy=0 solve this equations

Thank you for all help..

B/r - Oct 11th 2012, 09:59 PMMarkFLRe: Dif.Equations
For the first problem, use:

$\displaystyle xy'+y=\frac{d}{dx}(xy)$ and then integrate the equation with respect to*x*.